Middle Ear Salivary Choristoma: A Rare Case Report and Update on Congenital Associations, Facial Nerve Involvement, and Treatment Strategies - Young, Allen; Evans, Lauran; Ng, Matthew (Case Reports in Otolaryngology, 2020)
Salivary gland choristoma is an extremely rare middle ear mass and is hypothesized to be caused by second branchial arch developmental anomalies. We present a 14-year-old girl with Dandy–Walker syndrome and conductive hearing loss. Middle ear exploration revealed a large middle ear mass with absent incus and stapes and displaced facial nerve. The mass was completely excised with histological confirmation of salivary gland choristoma. Her hearing was improved with bone-anchored hearing aids (BAHA). As facial nerve involvement is common, physicians should consider partial excision to avoid facial nerve palsy. Hearing restoration can be achieved with OCR or BAHA.